PRAKTIK TANGGUNG JAWAB SOSIAL PERUSAHAAN DI PT. BAKRIE SUMATERA PLANTATIONS TBK. UNIT JAMBI - Suwandi, Suwandi; Keban, Yeremias T; Martono, Edi (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2013)
Companies all over the world have implemented corporate social responsibility. This research is aimed to analyze factors afecting CSR practice by Bakrie Sumatera Plantations Unit Jambi, a palm oil plantation company. The CSR practice was hypothesized to be infuenced by government regulation and corporate strategy. The primary data was collected through survey, interviews, focused group discussion, and direct observation in the feld. Meanwhile, the secondary data was gathered from various documents. The data was analyzed by using quantitative and qualitative approaches. The result shows that the government regulation CSR has no impact on the CSR practice. On the reverse, the corporate commitment and strategy were the decisive factors in the successful of CSR practice. This research also found that the CSR practice has contributed to the improvement of peopleÃ¢â‚¬â„¢s economic and social conditions. The prominent weakness is that the CSR policies and strategies were top-down and the participation of local people were limited. The other empirical fnding is that the nucleus-plasma partnership was able to implement the basic principles of CSR which were prevailing generally in diferent sector of businesses.Keywords :Ã‚Â government policy, corporate strategy, CSR practice, nucleus-plasma partnership, palm oil.